2017
DOI: 10.1097/icu.0000000000000330
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular lens calculations after laser vision correction

Abstract: Postrefractive patients undergoing cataract extraction and IOL implantation should have corneal measurements and IOL calculations that take into account and compensate for the limitations in accurate measurements and calculations. IOL selection should also aim to compensate for induced spherical aberration according to the ablation pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Several strategies have been proposed to overcome the errors in IOL power calculations, with the aim of improving refractive outcomes after cataract surgery in such patients. These strategies can be grouped into five categories: (1) methods that require prerefractive surgery data; (2) methods that calculate corneal power from postrefractive measurements; (3) using current corneal measurements with adjustment of IOL power; (4) direct measurements of anterior and posterior cornea after refractive surgery; (5) intraoperative IOL power determination 27. Methods using the first two categories are often limited in a real-life setting as historical data is often difficult or impossible to obtain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several strategies have been proposed to overcome the errors in IOL power calculations, with the aim of improving refractive outcomes after cataract surgery in such patients. These strategies can be grouped into five categories: (1) methods that require prerefractive surgery data; (2) methods that calculate corneal power from postrefractive measurements; (3) using current corneal measurements with adjustment of IOL power; (4) direct measurements of anterior and posterior cornea after refractive surgery; (5) intraoperative IOL power determination 27. Methods using the first two categories are often limited in a real-life setting as historical data is often difficult or impossible to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis concluded that the Masket method and the Shammas-PL performed better than the Haigis-L. The Barrett True-K formula is one of the more recently developed methods, and it can be used without historical data 26 27 43 44. Studies comparing it with other formulae after previous myopic LASIK or PRK suggested that it was at least equal to, and often better than, the other methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation